Fashion Micro-and Small Enterprise Frugal Innovation’s In Facing Covid 19 Pandemic - Siti Hasnaa Madinah; Ahmad Room Fitrianto (Relevance: Journal of Management and Business, 2023)
The aim of this study is to explore the business strategy in strengthening MSE’s resilience during pandemic Covid 19 using the six principles of frugal innovation. A qualitative study method employed with single case study at Saffana boutique Surabaya. The observation shows that Saffana boutique Surabaya was able to create more value and applied different approaches to explore strategy innovation in their product during the pandemic. The saffana boutique innovation framed using the six values of the frugal innovation, such as managing their cash flow in flexible way for mobilizing the existing and potential resource, utilizing social media and social project in order to engage and shape customer behavior and; develop the sustainable solution and fashion concept through collaboration with active customer to create new design based value and local culture; as well as make an effective networks with designer community and digital partners. All in all, this study has identified different approaches to explore strategy innovation and successful practices, which are related to strengthening the business resilience in severe condition.